School Head’s Professional Identity, Emotional Intelligence and Perfectionism: Three-Tier Factors to Advance Pedagogical Leadership - Callo, Eden C.; Asilo, Marta G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study is focused on the school head’s professional identity, emotional intelligence, and perfectionism as three tier factors to advance pedagogical leadership. The study employed the quantitative descriptive methodology, combining descriptive and multiple linear regression analysis. The researchers-made online survey instrument, via a google form. Responses from 132 school heads were analyzed using descriptive statistics such as mean, and standard deviation. Multiple linear regression analysis was employed to determine the significant relationships of the variables. The results reveal that professional identity has a positive relationship with pedagogical leadership. Contradicting result is the emotional intelligence which has a negative relationship with pedagogical leadership. Lastly, perfectionism has a positive relationship with pedagogical leadership. It is concluded that a school head’s professional identity, emotional intelligence and perfectionism significantly predict pedagogical leadership. Hence, the department (DepEd) may conduct series of training and workshops for teachers as a capacity building to equip them with knowledge and competencies to handle the numerous challenges in the delivery of quality, relevant, inclusive, and liberating education to the Filipino learners. Further, during Gender and Development programs one activity to consider is the training in emotional development among teachers and school heads.